Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1016/s0002-9440(10)63382-2
|View full text |Cite
|
Sign up to set email alerts
|

Smad3 Deficiency Ameliorates Experimental Obliterative Bronchiolitis in a Heterotopic Tracheal Transplantation Model

Abstract: Chronic allograft rejection manifested as obliterative bronchiolitis (OB) remains the single greatest impediment to long-term survival after lung transplantation. Transforming growth factor-␤1 (TGF-␤1) has been implicated in the tissue remodeling response associated with OB. Therefore, its intracellular signal transducer, Smad3, is a prime target of investigation. Herein, we examine the role of TGF-␤1, through Smad3, in the development of OB using heterotopic tracheal transplantation in wild-type and Smad3-nul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 38 publications
4
36
0
Order By: Relevance
“…Although studies by our group [12] and others [36] have shown the capacity of TGF-β1 to activate FAK in certain cell types, a role for SMAD3 in mediating this effect has not been previously demonstrated. The requirement for SMAD3 in FAK activation is consistent with a role for SMAD3 in myofibroblast differentiation both in-vitro [37,38] and in-vivo [39][40][41].…”
Section: Discussionsupporting
confidence: 73%
“…Although studies by our group [12] and others [36] have shown the capacity of TGF-β1 to activate FAK in certain cell types, a role for SMAD3 in mediating this effect has not been previously demonstrated. The requirement for SMAD3 in FAK activation is consistent with a role for SMAD3 in myofibroblast differentiation both in-vitro [37,38] and in-vivo [39][40][41].…”
Section: Discussionsupporting
confidence: 73%
“…Male Sprague Dawley (SD; Charles River Laboratories, Wilmington, MA) or Fischer 344 (F344; Harlan, Indianapolis, IN) donor rats (age, 3-5 mo) were fed the Lieber-DeCarli isocaloric liquid diet, containing either ethanol (36% total calories) or Maltin-Dextrin as substitute (control diet) for 8 weeks. HTT was performed as described previously (16). Briefly, isografts or allografts were obtained by transplanting tracheas from control or alcohol-fed donor rats subcutaneously into recipient rats.…”
Section: Htt Of Tracheas In Ratsmentioning
confidence: 99%
“…Allograft injury, as determined by epithelial loss, cellular infiltration, and collagen deposition within the lumen of the airway, was assessed at 3, 7, 14, and 21 days after transplantation, as described previously (16). Image analyses were performed as described by Schacker and colleagues (32).…”
Section: Histochemical Evaluation Of Oadmentioning
confidence: 99%
See 2 more Smart Citations